Vibrio splendidus O‐antigen structure: a trade‐off between virulence to oysters and resistance to grazers. (4th April 2020) - Oyanedel, Daniel; Labreuche, Yannick; Bruto, Maxime; Amraoui, Hajar; Robino, Etienne; Haffner, Philippe; Rubio, Tristan; Charrière, Guillaume M.; Le Roux, Frédérique; Destoumieux‐Garzón, Delphine
Summary: A major debate in evolutionary biology is whether virulence is maintained as an adaptive trait and/or evolves to non‐virulence. In the environment, virulence traits of non‐obligatory parasites are subjected to diverse selective pressures and trade‐offs. Here, we focus on a population of Vibrio splendidus that displays moderate virulence for oysters. A MARTX (Multifunctional‐autoprocessing repeats‐in‐toxin) and a type‐six secretion system (T6SS) were found to be necessary for virulence toward oysters, while a region (wbe) involved in O‐antigen synthesis is necessary for resistance to predation against amoebae. Gene inactivation within the wbe region had major consequences on the O‐antigen structure, conferring lower immunogenicity, competitive advantage and increased virulence in oyster experimental infections. Therefore, O‐antigen structures that favour resistance to environmental predators result in an increased activation of the oyster immune system and a reduced virulence in that host. These trade‐offs likely contribute to maintaining O‐antigen diversity in the marine environment by favouring genomic plasticity of the wbe region. The results of this study indicate an evolution of V . splendidus towards moderate virulence as a compromise between fitness in the oyster as a host, and resistance to its predators in the environment.